If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -2) = 4(x + -13) Reorder the terms: 2(-2 + x) = 4(x + -13) (-2 * 2 + x * 2) = 4(x + -13) (-4 + 2x) = 4(x + -13) Reorder the terms: -4 + 2x = 4(-13 + x) -4 + 2x = (-13 * 4 + x * 4) -4 + 2x = (-52 + 4x) Solving -4 + 2x = -52 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -4 + 2x + -4x = -52 + 4x + -4x Combine like terms: 2x + -4x = -2x -4 + -2x = -52 + 4x + -4x Combine like terms: 4x + -4x = 0 -4 + -2x = -52 + 0 -4 + -2x = -52 Add '4' to each side of the equation. -4 + 4 + -2x = -52 + 4 Combine like terms: -4 + 4 = 0 0 + -2x = -52 + 4 -2x = -52 + 4 Combine like terms: -52 + 4 = -48 -2x = -48 Divide each side by '-2'. x = 24 Simplifying x = 24
| -2x/9-8=-5 | | -75=87-43x | | 1/5(10x-3)-7 | | x+4x=906.25 | | -75=43x-87 | | 3.5=b/9 | | 10=-7x+8 | | -11-5a=66(5a+4) | | (6.6x)+4=50.2 | | 8/X=98/100 | | 88.1-2.3=-71 | | y+2x=-3yvalues | | 55/75=x100 | | 2x-3+x+5x+3+6x=40 | | 3+4x-16x=7 | | 36+(-61)= | | -17+(-9)= | | 3(3y-8)-2(y-7)= | | (8x-10x)(x-1)=0 | | 9x+15=4-2x | | 9x-7(x+2)=10 | | 9x-7(y+2)=10 | | 3x-3=4+2x | | y=ax^2+b | | 9x=4-2x | | y+(-39)=-43 | | 18=26x-34 | | 82+(-20)= | | 8x+13y=2700 | | 4x^2+9-45=0 | | ysinx-xy^2=c | | ysenx-xy^2=c |